Tirukkural - Chakravarti, A (Madras Diocesan Press, 1953)
TIRUKKURAL' which is called the Veda of the Tamils, is a book of universal importance. From the very fact that it is claimed by the various religious sects which have sprung up in South India, is a proof that it is acceptable to all. Various commentators belonging to various religious denominations wrote commentaries on the work according to their own predilections. The work is also translated into various European languages. Hence, it may appear at the outset that an English translation of the work at present may be unnecessary and superfluous. But there is a justification for this procedure. There is an interval of several centuries between the composition of the original and the appearance of the commentaries. The various commentators appear long after the disappearance of the original culture and civilisation whose picture is presented in the original. Hence, it is necessary to emphasise the fundamental ideal in the original background, viz the ideal of ahimsa.
With english translation and commentary and an introduction.
Keywords: Social Process